2018
DOI: 10.1021/acsabm.8b00385
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Mechanism of Stabilization and Microstructure of Oil-in-Water Emulsions by Native Cellulose Microfibrils in Primary Plant Cells Dispersions

Abstract: It is long known that oil-in-water emulsions can be stable against coalescence in homogenized plant cell wall dispersions due to the presence of surface active biopolymers. When plant cell wall material is homogenized to the extent of deagglomeration of the cellulose microfibrils (CMFs), a much more complex dispersed system is obtained. Here we show that in such complex systems both surface active soluble polymers and individual CMFs are at the origin of this stabilization against coalescence, as they form a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…After extraction from natural vegetal sources, it can be isolated under different insoluble forms and thereafter used without further modification to stabilize Pickering emulsions. Indeed, by physical destructuration it is possible to isolate microfibrils (CMF), themselves constituted of nanofibrils (CNF), and by acid hydrolysis of the amorphous parts of these respective fibers one can obtain microcrystals (MCCs) and nanocrystals , (CNCs), the latter being purely crystalline objects. It has been demonstrated that these objects are highly hydrophilic but present amphiphilic properties thanks to their surface chemistry. , As their surface presents a lot of hydroxyl functions, chemical modification is easy to perform.…”
Section: Organic Particles With Natural Origin As Pickering Emulsion ...mentioning
confidence: 99%
“…After extraction from natural vegetal sources, it can be isolated under different insoluble forms and thereafter used without further modification to stabilize Pickering emulsions. Indeed, by physical destructuration it is possible to isolate microfibrils (CMF), themselves constituted of nanofibrils (CNF), and by acid hydrolysis of the amorphous parts of these respective fibers one can obtain microcrystals (MCCs) and nanocrystals , (CNCs), the latter being purely crystalline objects. It has been demonstrated that these objects are highly hydrophilic but present amphiphilic properties thanks to their surface chemistry. , As their surface presents a lot of hydroxyl functions, chemical modification is easy to perform.…”
Section: Organic Particles With Natural Origin As Pickering Emulsion ...mentioning
confidence: 99%
“…There are two main hypotheses for the stabilizing mechanism of Pickering emulsions stabilized with BC/CCS: (1) the hybrid particles are adsorbed at the oil–water interface and resulted in a two or three-dimensional network between emulsion droplets, which inhibit its free movement and coalescence; (2) the deposited particles can form a solid interfacial film around the oil droplet to enhance the steric barrier between the droplets, which can further prevent coalescence and enhance the stability of the Pickering emulsions. Compared with other emulsion systems, the resultant emulsion stabilized with BCNFs and CCS exhibited long-term excellent storage stability. …”
Section: Resultsmentioning
confidence: 99%
“…Depletion effects of the nonadsorbed CNFs explain the stability of the emulsions against creaming. 15…”
Section: Results and Discussionmentioning
confidence: 99%